Significant up-regulation of lncRNAs in neuromyelitis optica spectrum disorder - Taheri, Mohammad; Sadeghi, Ahmad; Gharebaghi, Alireza; Ghiasian, Masoud; Eslami, Solat; Khalilian, Sheyda; Sayad, Arezou; Ghafouri-Fard, Soudeh (Scientific reports, 2023)
Neuromyelitis optica spectrum disorder (NMOSD) is an immune-related demyelinating defect. Long non-coding RNAs (lncRNAs) might influence the pathobiology and progression of NMOSD. The current study assessed expression level of NEAT1, PANDAR, MEG3 and TUG1 lncRNAs in the peripheral blood of NMOSD patients compared with healthy individuals. All mentioned lncRNAs were shown to be over-expressed in total NMOSD cases, male NMOSD cases and female NMOSD cases compared with the matching control subgroups. MEG3 had the most robust over-expression in patients subgroups compared with normal subjects. There was no noteworthy difference in the expression of any of lncRNAs between female and male patients. MEG3 had an ideal performance in the differentiation of NMOSD cases from healthy persons (Sensitivity and specificity values = 100%). Other lncRNAs could also efficiently separate NMOSD cases from control subjects (AUC values = 0.97, 0.89 and 0.88 for PANDAR, NEAT1 and TUG1, respectively). Cumulatively, NEAT1, PANDAR, MEG3 and TUG1 lncRNAs can be considered as appropriate disease markers for NMOSD.